"Doctor, how long will it take?" Results from an historical cohort on surgical pressure ulcer healing delay and related factors in persons with spinal cord injury. Issue 2 (May 2021) - Gelis, Anthony; Morel, Juliette; Amara, Bouali; Mauri, Cécile; Rouays, Hélène; Verollet, Christine; Almeras, Isabelle; Frasson, Nicolas; Dupeyron, Arnaud; Laffont, Isabelle; Daures, Jean-Pierre; Herlin, Christian
Abstract: Background: Flap surgery for deep pelvic pressure ulcers has already shown its effectiveness. Most studies relating to the postoperative period assessed complications rates and associated risk factors, but none focused on delayed wound healing. The objective of this study was to describe wound healing delay after primary flap surgery in patients with spinal cord injury (SCI) and to assess associated risk factors. Methods: This observational retrospective study based on medical charts included all persons with SCI operated for primary flap surgery for pelvic PU in the Hérault department of France between 2006 and 2014. Overall, 100 biomedical, psychological, socioeconomics and care management factors were studied. The primary outcome was wound healing delay, defined as time from surgery to complete cutaneous closure. Results: 85 patients were included. Median healing time was 48 days (R: 20–406). Healing rate was 70% at 3 months and 90% at 4 months. After a multivariate analysis three factors were significantly associated with delayed wound healing: duration of hospitalization in the acute care unit (HR = 2.68; p = 0.004), local post-operative complication (HR = 10.75; p = 0.02), and post-operative sepsis (HR = 2.18; p = 0.02). Conclusion: After primary skin flap surgery for PU in persons with SCI, delayed wound healing is related to local or general complications as well as care management organization. The risk of delayed wound healing justifies the implementation of a coordinated pre-operative management to prevent complications and a structured care network for an earlier transfer to a SCI rehabilitation center. Highlights: After primary flap surgery for PU, median healing delay is 48 days in persons with spinal cord injury. The main risk factor for delayed healing is local post-operative complications. Healing delay might be improved by a proper post-surgical bacteriological management, and a early transfer in a SCI rehabilitation unit.